2013
DOI: 10.2460/javma.243.8.1129
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of rabies in bats in Texas (2001–2010)

Abstract: Information on the epidemiology of rabies in bats and the epidemiology of exposures to rabid bats may be useful in planning and implementing local, state, and national rabies control and prevention campaigns and in encouraging rabies vaccination of domestic animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 11 publications
4
16
0
Order By: Relevance
“…Nonbite exposures accounted for the majority (48%) of submissions, with unspecified exposures and bite exposures accounting for fewer submissions (31% and 21%, respectively). Nonbite exposures were also responsible for the majority of submissions annually and by month, similar to studies of bat rabies in Colorado and Texas (Pape et al 1999;Mayes et al 2013). The risk of contact with rabid bats was highest for bite exposures and is similar to results obtained from a Colorado study (Pape et al 1999), yet the risk of contact with rabid bats was also high in this study among cases where exposure was reported but unspecified (Table 3).…”
Section: Species Composition Of Submissions Insupporting
confidence: 84%
See 4 more Smart Citations
“…Nonbite exposures accounted for the majority (48%) of submissions, with unspecified exposures and bite exposures accounting for fewer submissions (31% and 21%, respectively). Nonbite exposures were also responsible for the majority of submissions annually and by month, similar to studies of bat rabies in Colorado and Texas (Pape et al 1999;Mayes et al 2013). The risk of contact with rabid bats was highest for bite exposures and is similar to results obtained from a Colorado study (Pape et al 1999), yet the risk of contact with rabid bats was also high in this study among cases where exposure was reported but unspecified (Table 3).…”
Section: Species Composition Of Submissions Insupporting
confidence: 84%
“…While some areas of the US have dramatically higher submission rates of bats per human population (Patyk et al 2012), it is unclear whether this reflects a real geographic difference in the incidence of exposure to bats. Regardless, data generated from passive surveillance are highly sensitive to human presence and behavior, as supported by associations between the population size of a county and the number of submissions and rabid bats detected in this study and by results from a Texas study reporting higher submissions and numbers of rabid bats from urban compared with rural localities (Mayes et al 2013). Despite this observation, the two bat-associated human rabies cases in Tennessee did not occur in counties with the highest number of submissions or rabid bats (Fig.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations